Spontaneous mystical experience among atheists: meaning-making, psychological distress, and wellbeing. - van der Tempel, Jan; Moodley, Roy (Mental Health, Religion & Culture, 2020)
In religious individuals, spontaneous mystical experiences (SMEs) tend to reinforce pre-existing beliefs and are associated with enhanced wellbeing, mediated by adaptive interpretive frameworks and accepting social environments. The meaning-making and outcomes of SMEs among atheists have not been investigated to date. Using a grounded theory approach, the present study found that the SMEs of eight male and female atheists of diverse backgrounds resembled those of religious experiencers in phenomenal content, but differed with respect to appraisal, coping, and outcome. Challenges in reconciling the SME with secular views and values were common and linked to varying degrees and durations of psychological distress, especially in relation to negative reactions from the social environment. No participant embraced organised religion, but most adopted more agnostic or spiritual worldviews, and ultimately associated their SMEs with enhanced wellbeing in various domains. However, participants who reported persisting doubt and preoccupation about their SMEs experienced deteriorating mental health.